The relationship between pain intensity and sleep quality in various type of elective postoperative patients at Prof. Dr. Chairuddin P. Lubis USU Medan Hospital - Tarigan, Randi Joel Oktavianus; Lubis, Andriamuri Primaputra; Ardinata, Dedi; Ketaren, Aga Shahri Putera (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Postoperative pain arises after surgery and includes acute pain that needs to be treated immediately. The postoperative phase must always be observed because it relates to the patient's recovery process. The prevalence of postoperative pain varies widely around the world, with the United States at 86%, Europe at 70%, and China at 48.7%. The prevalence of postoperative pain in Indonesia has not been studied as a whole.Objectives: The research aims to analysed the relationship between pain intensity and sleep quality in elective postoperative patients at Prof. dr. Chairuddin P. Lubis USU Medan Hospital.Methods: The research used an analytical observation using a cross-sectional approach with a consecutive sampling design. Respondents' data was collected only once and simultaneously using the Numeric Pain Rating Scale (NRS) and Pittsburgh Sleep Quality Index (PSQI) questionnaires. The data will be analysed using the Statistical Package for the Social Sciences (SPSS), including Somers'd test.Results: Based on the analysis of 125 respondents' data, the highest experienced pain intensity by patients was moderate pain intensity with 49,6%, mild pain intensity with 38,4%, and severe pain intensity 12%. In the sleep quality, the poor sleep quality group was the highest, with 54,4% and the good sleep quality group 45,6%. Respondents in this research were majority aged 26–35 years with 37 respondents. This analysis shows a significant relationship and very strong correlation between pain intensity and sleep quality (p-value <0,001 and r = 0,789).Conclusion: There is a relationship between pain intensity and sleep quality in elective postoperative patients at Prof. dr. Chairuddin P. Lubis USU Medan Hospital.